3(6x+4)-3x+8=49

Simple and best practice solution for 3(6x+4)-3x+8=49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(6x+4)-3x+8=49 equation:


Simplifying
3(6x + 4) + -3x + 8 = 49

Reorder the terms:
3(4 + 6x) + -3x + 8 = 49
(4 * 3 + 6x * 3) + -3x + 8 = 49
(12 + 18x) + -3x + 8 = 49

Reorder the terms:
12 + 8 + 18x + -3x = 49

Combine like terms: 12 + 8 = 20
20 + 18x + -3x = 49

Combine like terms: 18x + -3x = 15x
20 + 15x = 49

Solving
20 + 15x = 49

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + -20 + 15x = 49 + -20

Combine like terms: 20 + -20 = 0
0 + 15x = 49 + -20
15x = 49 + -20

Combine like terms: 49 + -20 = 29
15x = 29

Divide each side by '15'.
x = 1.933333333

Simplifying
x = 1.933333333

See similar equations:

| 2j=3j+9 | | -276=12b | | 17*4=n | | -27=4v-7 | | 0.625(8+c)=-20 | | 5x+7+9x-63+4=180 | | 89=-p | | (6s*4.5)+2d=(5s*4.5)+5d | | 4u+4=12 | | (2)/(7)x-(3)/(5)x=(3)/(7)x-(2)/(5) | | M+9=70 | | 6-1/3×=1 | | 4/5x^2-3=77 | | 2x+21+11=x+23 | | 21-x=48 | | T+8=-76 | | 14y-6=11y-27 | | 5x+7+9x-63= | | 3.2k=49 | | 3/4x5= | | 24uw^2y^4-28u^6w^9=0 | | G+73=15 | | (6r+2+8r^3)-(5r^3-11-8r^5)-(6r+9r^5)=0 | | 38+-3=50+-5x | | I=122m | | 45/10=x/54 | | 4t+6t-7= | | 2q=-16 | | 5x+7+9x-63=60 | | 4x-5x^2=-x^3 | | -3t=-6 | | 3x+21-2y=3 |

Equations solver categories